Left ventricular noncompaction diagnosis and management relevant to pre-participation screening of athletes - Caselli, S.; Attenhofer Jost, C. H.; Jenni, R.; Pelliccia, A. (The American Journal of Cardiology, 2015)
Left ventricular noncompaction (LVNC) has been extensively studied over the last years, and an increasing number of cases have been reported worldwide, with a large proportion comprising young and asymptomatic subjects, including athletes. The current epidemic of LVNC is likely the consequence of several causes, that is, the increased awareness of the disease and the refined cardiovascular imaging techniques. The current diagnostic methods, based uniquely on definition of morphologic findings, do not always resolve the overlap of a physiological myocardial architecture comprising a prominent trabecular pattern from a mild phenotypic expression of the real disease. Appropriate criteria for identification and management of LVNC in athletes have, therefore, become a novel challenge for cardiologists and sport physicians, who are required to solve the question of diagnosis and appropriate management in the setting of pre-participation cardiovascular screening. Indeed, although it is important to timely identify a true myocardial disease, to reduce the burden of adverse cardiac event in a young athlete, in contrast, a misdiagnosis of LVNC may lead to unwarranted restriction of the athlete lifestyle, with detrimental psychological, social, and economic consequences. This review report has been planned, therefore, to help physicians in diagnosing and managing athletes presenting with a morphologic pattern suggestive of LVNC with specific focus on criteria for advising sport participation.